2015
DOI: 10.1007/s11356-015-5036-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute and sub-chronic toxicity of four cytostatic drugs in zebrafish

Abstract: The acute and sub-chronic effects of four cytostatic drugs-5-fluorouracil (5-FU), cisplatin (CisPt), etoposide (ET) and imatinib mesylate (IM)-on zebrafish (Danio rerio) were investigated. Acute tests were carried out in a static system in accordance with the OECD guideline 203 for adult fish and the draft guideline for fish embryos (FET test) in order to find the LC50 values of the four cytostatic drugs. Early-life stage toxicity test on zebrafish was conducted according the OECD guideline 210 using the cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 40 publications
2
19
2
Order By: Relevance
“…In contrast, no negative effects of diclofenac on embryo development have been reported in common carp (Stepanova et al, ) and brown trout (Schwarz et al, ). In ecotoxicological assays of chemicals, zebrafish are increasingly used to examine abnormal embryogenesis, and there are many reports that abnormal embryogenesis is induced in zebrafish by various chemicals including agricultural chemicals (Cao et al, ; Jia, Mao, Zhang, Zhang, & Jiang, ; Maharajan, Muthulakshmi, Nataraj, Ramesh, & Kadirvelu, ; Sulukan et al, ; Yao, Yu, Zhou, Xiang, & Xu, ), pharmaceuticals (Chen et al, ; Félix et al, ; Kovács et al, ; present study) and metals (Horie, Yamagishi, Koshio, et al, ; Sun et al, ; Yin et al, ). These studies suggest that zebrafish embryos are particularly sensitive to chemical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no negative effects of diclofenac on embryo development have been reported in common carp (Stepanova et al, ) and brown trout (Schwarz et al, ). In ecotoxicological assays of chemicals, zebrafish are increasingly used to examine abnormal embryogenesis, and there are many reports that abnormal embryogenesis is induced in zebrafish by various chemicals including agricultural chemicals (Cao et al, ; Jia, Mao, Zhang, Zhang, & Jiang, ; Maharajan, Muthulakshmi, Nataraj, Ramesh, & Kadirvelu, ; Sulukan et al, ; Yao, Yu, Zhou, Xiang, & Xu, ), pharmaceuticals (Chen et al, ; Félix et al, ; Kovács et al, ; present study) and metals (Horie, Yamagishi, Koshio, et al, ; Sun et al, ; Yin et al, ). These studies suggest that zebrafish embryos are particularly sensitive to chemical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to their mechanisms of action most of these drugs are genotoxic, carcinogenic, and/or teratogenic and can cause adverse effects in aquatic organisms, especially upon chronic exposure ( Kuemmerer & Ruck, 2014 ; Toolaram, Kuemmerer & Schneider, 2014 ). Several recent studies demonstrated that certain antineoplastic drugs cause adverse effects to different aquatic species even at concentrations relevant for aquatic environment ( Brezovšek, Eleršek & Filipič, 2014 ; Elersek et al, 2016 ; Kovacs et al, 2015 ; Kovacs et al, 2016 ; Misik et al, 2014 ; Parrella et al, 2014 ; Parrella et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dose‐response studies were conducted with the aforementioned nominal waterborne concentrations of cisplatin based on previous findings in the literature (Kovács et al, ). Lethality and a delayed hatching endpoint were analytically evaluated (Figure ).…”
Section: Resultsmentioning
confidence: 99%